Social Media Sociolinguistics: Patterns, Trends, And The Dynamics Of Digital Language - Isnarini, Eka; Khaeruman; Muti'ah, Eva (Center of Language and Cultural Studies, 2024)
The development of digital technology has changed a person's mindset in communicating, especially in terms of social media. This study examines the mindset, trends and dynamics of digital language in the context of social media. The purpose of this study explores how digital language influences social media, including the use of words, language and the dynamics of interaction between social media users. The analysis method used in this study is a literature review, covering various reference sources that are in accordance with the topic discussed. The results of the analysis show that social media has unique patterns and trends, which are influenced by many factors such as cultural background, gender to age and the interaction of social media users can affect language development.